2019
DOI: 10.1002/adfm.201808961
|View full text |Cite
|
Sign up to set email alerts
|

Biospecific Monolayer Coating for Multivalent Capture of Circulating Tumor Cells with High Sensitivity

Abstract: The isolation and detection of rare circulating tumor cells (CTCs) from patient peripheral blood can help to monitor the metastatic spread of carcinoma and evaluate therapeutic outcomes. However, it is technically challenging to isolate CTCs due to extreme rarity in blood. Current techniques typically have to utilize complex instrumentation to capture CTCs, resulting in nonapplicability. Inspired from the mussel adhesion, a polyglycerol-based block polymer is used to fabricate a biospecific and bioinert interf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 55 publications
0
17
1
Order By: Relevance
“…[45] It is worth noting that a higher yield was observed for low EpCAM-expressed cells (MDA-MB-231) captured by DNA nanosynapse (≈77.0%), compared to topologydefined isotropous aptamers (≈29.8%) and other EpCAM-based methods ( Figure 2B; Table S2, Supporting Information). [25,[45][46][47] However, previously published work by Zuo et al reported a 75% capture efficiency toward MDA-MB-231 cells using TDN-3 EpCAM, which was much higher than what we had observed (Table S3, Supporting Information). [42] This was attributed to the differences in experiment procedure where we co-spiked cells with 10 5 Jurkat cells in PBS, rather than pure PBS adopted by previous work.…”
Section: Magnetic Capture Toward Heterogeneous Cellscontrasting
confidence: 53%
See 1 more Smart Citation
“…[45] It is worth noting that a higher yield was observed for low EpCAM-expressed cells (MDA-MB-231) captured by DNA nanosynapse (≈77.0%), compared to topologydefined isotropous aptamers (≈29.8%) and other EpCAM-based methods ( Figure 2B; Table S2, Supporting Information). [25,[45][46][47] However, previously published work by Zuo et al reported a 75% capture efficiency toward MDA-MB-231 cells using TDN-3 EpCAM, which was much higher than what we had observed (Table S3, Supporting Information). [42] This was attributed to the differences in experiment procedure where we co-spiked cells with 10 5 Jurkat cells in PBS, rather than pure PBS adopted by previous work.…”
Section: Magnetic Capture Toward Heterogeneous Cellscontrasting
confidence: 53%
“…To address the above issue, many methods based on cocktail of various capture ligand had been exploited for the accurate capture of CTCs. [24,25] To date, the successful improvement of capturing heterogeneous CTCs via cocktail of aptamers was achieved by decorating different aptamers on the same substrates. [26,27] However, the conformation of aptamers would be affected by the interaction between substrates and aptamers, leading to limited capture performance.…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16][17] In order to satisfy the ultimate purpose of CTCs enrichment with high purity and high efficient, two essential terms, the antifouling surface and immobilized monoclonal-antibodies/aptamers, are particularly required in design and fabrication of the sophisticated magnetic capture platforms. More specifically, the antifouling surface eliminates non-specific adsorption of non-CTCs or proteins in the CTCs recognition and binding stage, [18][19][20] and the monoclonal-antibodies/aptamers provide an immunoaffinity channel to recognize/bind specific antigens, complement components, and receptors on CTCs membranes. [3,6] Taken together, highly purified CTCs can be captured with high yield as far as possible.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12][13] Among them, the methods based on affinity interaction between the bioligands at the interfaces and the biomarkers on cancer cell membrane yield higher efficiency and good specificity in contrast to mechanical and electrical sorting technique. [14] But it is still difficult to isolate the CTCs with higher purity and viability. [15] Recently, increasing evidence indicates that biomimetic micro/nano topographic features at the cell-material interface could greatly improve the CTCs capture efficiency from patient blood.…”
Section: Doi: 101002/adhm202002202mentioning
confidence: 99%